POTENSI GULMA ECENG PADI (Monochoria vaginalis) SEBAGAI TANAMAN HIAS: Potential Of Rice Water Weed (Monochoria Vaginalis) As Ornamental Plants - E. A. Syaifudin; Nimatuljannah Akhsan; Suyadi Suyadi; F Syahrianto (Fakultas Pertanian Universitas Palangka Raya, 2022)
Water hyacinth weeds can cause disturbances in the form of silting and increase competition with other plants. On the other hand, water hyacinth has purple flowers, very beautiful when it blooms quite a lot, it can be used as an ornamental plant that refreshes the view and adds aesthetic value. This study aimed to assess the potential of water hyacinth (Monochorea vaginalis) as an ornamental plant and to see the response of water hyacinth to the application of Gandasil D. This study was designed in a t-test that was not given Gandasil D (P0) fertilizer and was given Gandasil D (P) fertilizer. Assessing the potential of rice water as an ornamental plant, a questionnaire was conducted on 20 respondents. Parameters observed for fertilization response were plant height, number of leaves, number of seeds and number of flowers. Data were analyzed using a t-test comparison at the 5% level. The results showed that the color of the rice water flower has a beauty value and has an aesthetic value, so this plant has the potential as an ornamental plant, and it is necessary to protect the rice water plant against plant pest organisms. The application of fertilizer to water hyacinth (Monochoria vaginalis) had no effect on plant height, number of leaves, number of seeds and number of flowers.